Buckwheat germplasm in the world - Zhou, Meiliang; Kreft, Ivan; Suvorova, Galina; Tang, Yu; Woo, Sun-Hee (Academic Press, 2018)
Buckwheat Germplasm in the World offers an overview of this globally important crop, including its general characterization and genetic diversity-particularly in Russia, China, India and Eastern Europe. The book presents the latest research on molecular marker development, genetics and phenotype analysis of new wild buckwheat to examine the nutritional values of this pseudocereal crop. Due to its short growth span, ability to grow at high altitudes and the high quality of its protein content, buckwheat is considered an important crop for addressing global food needs. Ideal for researchers and advanced-level students seeking better understanding of the buckwheat germplasm.